A operacionalização da política de governança na administração pública federal - Girardi, Jeferson (2019)
The historical context in the public sector brings a set of administrative changes with a view to explaining the relations between the State, the government and society. Public governance emerges as the movement with the aspiration to meet, in addition to the managerial and administrative performance and the competence of the State to execute public policies, the dimension of civil society performance as a political actor. This study deals with the examination of the characteristics of public governance in order to define the phenomenon and how the Brazilian Federal Public Administration conceives it from the implementation of the public governance policy of 2017. The methodological approach adopted was the qualitative, descriptive, applied, outlined in a case study, with technical procedures for bibliographical and documentary research, complemented by content analysis. For this analysis, Decree No. 9.203/2017, the Guide to the Governance Policy of the Civil House of the Presidency of the Republic, and the Ordinances establishing the internal committees in three organizations of the federal public administration were consulted: Ministry of Education, Ministry of Industry, Foreign Trade and Services and the National Institute of Social Security. The results highlight the exposition of the concepts of public governance, its principles, guidelines and components; the emphasis on the techno-bureaucratic structure of the research target public organizations, highlighting the merit that the governance component as a government capacity has in the debate; and finally the analysis of the contents of the legal instruments that demarcate the institution and operationalization of the governance policy for the federal public administration, and reflect the conception of public governance adopted by the state apparatus.